Decoupled payments to EU farmers, production, and trade: An economic analysis for Germany - Harald von Witzke; Steffen Noleppa; Gerald Schwarz (Humboldt-Universität zu Berlin, Wirtschafts- und Sozialwissenschaften an der Landwirtschaftlich-Gärtnerischen Fakultät, 2010)
After an extended process of reform the European Union has introduced direct payments to farmers which are decoupled from production decisions as a central element of its Common Agricultural Policy. They are also referred to as Single Farm Payments. In this paper we analyze the production and trade effects of this policy and its compatibility with WTO international trade rules. A survey of the literature suggests that the system of direct payments in its present form has effects which are analogous to a subsidization of agricultural land. Thus, they act to increase production and trade. Furthermore we quantify the total economic cost of production of selected commodities in the European Union and compare them to the price at which EU production is sold in foreign markets. Our analysis suggests that the costs of production in the European Union for key agricultural commodities are below international prices. It can be established that commodities for which the European Union is a net exporter are sold below cost, for extended periods of time and in substantial quantities. The EU system of decoupled payments to farmers, thus, acts to inflict economic injury to third countries. Under WTO rules, dumping can only occur when a country is an exporter. In this paper we demonstrate that on the markets included in the analysis dumping occurs on the market for wheat. The extent of injury is exemplified for Australia. – – Im Zuge des Reformprozesses der Gemeinsamen Agrarpolitik der Europäischen Union wurden als zentrales Instrument schließlich Direktzahlungen an die Landwirtschaft eingeführt, die von den tatsächlichen Produktionsentscheidungen entkoppelt sind. In diesem Beitrag wird analysiert, welche Produktions- und Handelseffekte durch diese Direktzahlungen an die Landwirtschaft verursacht werden und wie diese im Licht der WTO Handelsregeln zu beurteilen sind. Eine Auswertung der Literatur zeigt, dass die Direktzahlungen wie eine Subvention auf den Bodeneinsatz wirken und diese daher Produktionseffekte aufweisen. Darüber hinaus werden in diesem Beitrag die Produktionskosten in Deutschland für ausgewählte Agrargüter quantifiziert und mit den Weltmarktpreisen verglichen. Dabei zeigt sich, dass selbst unter sehr konservativen Annahmen die Produktionskosten oberhalb der Weltmarktpreise liegen. Bei Weizen ist die EU Nettoexporteur und erfüllt daher die WTO Kriterien für Dumping. Der Umfang der ökonomischen Kosten dieser Politik bei Weizen wird am Beispiel Australiens quantifiziert.
Keywords: 330; European Union; Common Agricultural Policy; WTO rules; decoupled payments; Europäische Union; Gemeinsame Agrarpolitik; WTO Regeln; entkoppelte Direktzahlungen; EU-Agrarpolitik; Reform; Agrarsubvention; Wirkungsanalyse; Agrarproduktion; Agraraußenhandel; WTO-Recht; Dumping; EU-Staaten